JANENGAN SEBAGAI SENI TRADISIONAL ISLAM-JAWA - Junaidi, Akhmad Arif (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
This paper is based on the cultural reality of Javanese Muslim society especially in Islamic Javanese traditional music. The cultural expression of Islamic-Javanese music is very diverse and reflecting the diversity of the “face” of Islam that has been adapted to the local culture. Janengan’s Islamic Javanese traditional music is an expression from three different cultural music traditions: Javanese music tradition, Middle Eastern music traditions (Arabic), and currently has been developed with a combination of Western music such as pop. The combination of three different musical traditions creates a unique creativity in Javanese music character. The character also encourages the values covering musical values, cultural values, and religious values. Thematically, the Janengan’s lyrics contain a variety of Islamic teaching such as monotheism, shari’ah and sufism.***Tulisan ini dilatarbelakangi satu realitas budaya yang dihasilkan dari kehidupan masyarakat Muslim Jawa khususnya seni musik tradisional Islam-Jawa. Ekspresi kebudayaan Islam-Jawa dalam seni musik ini sangat beragam dan mencerminkan keberagaman “wajah” Islam yang telah beradaptasi dengan budaya lokal. Musik tradisional Islam-Jawa Janengan merupakan perwujudan dari perpaduan tiga unsur tradisi musik, yakni tradisi musik Jawa, tradisi musik Islam Timur Tengah (Arab) dan kini telah dikembangkan dengan kombinasi musik Barat seperti pop. Perpaduan ketiga unsur tradisi musik yang berbeda ini membentuk suatu hasil kreativitas yang unik bercirikan musik Jawa. Musik tradisional Islam-Jawa ini juga melahirkan nilai-nilai yang meliputi nilai-nilai musikal, nilai-nilai kultural, dan nilai-nilai religius. Secara tematik syair-syair Janengan berisi berbagai ajaran seperti akidah (tauhid), syari’at dan tasawuf.